Challenges on the Follow-Up Experimental Leptospiral Infection in Sheep - Rocha, Bruno Ribeiro; da Rosa, Matheus Costa; Correia, Lucas; Martins, Gabriel; Dellagostin, Odir Antônio; Lilenbaum, Walter (Acta Scientiae Veterinariae, 2019)
Background: Leptospirosis is currently a source of significant economic losses in the agribusiness; as such, experimental studies on this infection are required to develop a better understanding of the pathogenesis, treatment, and immunoprophylaxis of the disease. Sheep may represent a good model for ruminants in such models. Despite the extent of the studies that has been conducted thus far, researchers have yet to reach a consensus on the experimental practices to apply for leptospirosis in this animal species, and several gaps in understanding remain. To bridge these gaps, the present study aimed to assess the usage of several tools for the monitoring of experimental leptospirosis in sheep. Material, Methods & Results: Twelve Santa Ines sheep of different ages were each allocated to one of four groups (A, B, C, and D). The subjects in groups A, B, and C received different doses of Leptospira interrogans serogroup Icterohemorrhagiae by intraperitoneal route, 1x102, 1x105, and 1x108 respectively. Group D was the control. Hematological, biochemical and clinical parameters were evaluated daily. Serology by microscopic agglutination test (MAT) and PCR were performed to evaluate the infection status. The most remarkable clinical signs were fever (41ºC) and dehydration, and acute pain (cub). Two animals from Group C presented leukocytosis. Only those in Group C exhibited positive results according to serology, while positivity in PCR was observed in animals in groups A and C. The results of the experiment indicated that sheep may be experimentally infected and can, therefore, be used as a model for leptospirosis in ruminants. Clinical signs cannot be considered to represent a reliable parameter for evaluating the development of leptospirosis in experimentally infected sheep. We recommend the use of urine PCR and serology to confirm the infection in experimentally infected animals and daily complete blood count (CBC) as a follow-up tool. Discussion: It was observed that the clinical signs cannot be considered as a reliable parameter to evaluate the pathogenesis in experimentally infected ewes, being important to emphasize that the age of the animals does not seem to alter their susceptibility to the infection. This finding is in agreement with other experimental studies, which report that leptospirosis infection in ruminants occurs asymptomatic and subclinical. Hematological and biochemical tests proved to be adequate tools to monitor the experimental infection. Studies have shown that the complete blood count has been used to monitor the acute phase of leptospirosis and is effective in detecting anemia and leukocytosis with neutrophilia in ruminants. Despite the lack of clinical signs, the serological and molecular results confirmed the experimental infection. PCR has been used as an important tool in the diagnosis of leptospirosis. In addition, the current study is the first of its kind to use PCR to detect the carrier status in experimentally infected ewes. Despite this limitation, PCR was very effective in confirming the infection and should be considered for use in experimental studies. Sheep have been used as a good experimental model in several studies, sheep are relatively small compared to other ruminants and can be easily allocated in smaller pens and pens, facilitating the management of research and minimizing the costs of experimentation. In this context, we suggest that sheep represent a good model for the study of leptospirosis in ruminants and therefore a reliable protocol for experimental infection by leptospirosis is necessary.